Postgraduate midwifery education programs to enhance clinical competency - Shafiah Shafiah; Ari Indra Susanti (Universitas Pendidikan Indonesia, 2025)
Strengthening clinical skills among midwives is essential for improving the quality of maternal and newborn care. This review aims to map and describe various postgraduate clinical education models designed to enhance midwifery competencies. The research was motivated by the increasing global demand for skilled midwives capable of addressing complex maternal and neonatal health issues. A systematic search was conducted in ScienceDirect, SpringerLink, PubMed, and Google Scholar for articles published between 2021 and 2025, focusing on studies that involved midwives and postgraduate clinical training. The review followed the PRISMA-ScR framework to ensure a rigorous selection and analysis process. The findings were grouped into three main themes: first, programs such as fellowships and advanced clinical placements contributed to improved clinical reasoning, leadership, and engagement with health systems; second, residency and internship models supported a smoother transition to clinical practice and encouraged interprofessional collaboration; third, preceptorship and mentorship approaches increased learners’ confidence, satisfaction, and skill integration through guided supervision and peer learning. These results underscore the crucial role of structured postgraduate clinical education in equipping midwives for the evolving demands of healthcare. Abstrak Peningkatan keterampilan klinis bidan sangat penting untuk memperbaiki kualitas pelayanan kesehatan ibu dan bayi baru lahir. Penelitian ini bertujuan untuk memetakan dan mendeskripsikan berbagai model pendidikan klinis pascasarjana yang dirancang guna meningkatkan kompetensi bidan. Kebutuhan global akan bidan yang terampil dalam menghadapi tantangan kesehatan ibu dan neonatal yang semakin kompleks menjadi alasan utama dilakukannya kajian ini. Peneliti melakukan penelusuran sistematis pada database ScienceDirect, SpringerLink, PubMed, dan Google Scholar untuk artikel yang diterbitkan antara tahun 2021 hingga 2025, dengan fokus pada studi yang melibatkan bidan dan pelatihan klinis pascasarjana. Proses telaah mengikuti pedoman PRISMA-ScR untuk memastikan seleksi dan analisis data yang ketat. Hasil kajian dikelompokkan dalam tiga tema utama: pertama, program seperti fellowship dan advanced clinical placement meningkatkan penalaran klinis, kepemimpinan, serta keterlibatan dalam sistem kesehatan; kedua, model residensi dan magang membantu transisi ke praktik klinis dan mendorong kolaborasi antar profesi; ketiga, pendekatan preceptorship dan mentorship meningkatkan kepercayaan diri, kepuasan, serta integrasi keterampilan peserta melalui supervisi dan pembelajaran sebaya. Temuan ini menegaskan pentingnya pendidikan klinis pascasarjana yang terstruktur dalam mempersiapkan bidan menghadapi tuntutan layanan kesehatan modern. Kata Kunci: kebidanan; kompetensi klinis; pendidikan pascasarjana